Flamingeld (flash flood mitigation warning shield) as risk reduction of losing the victims' properties and life / Muh. Khadafi Kasim ... [et al.] - Kasim, Muh. Khadafi; Zainurrahman, Muhammad; Alimurrijal, Islamuddin; Karti'a, Galuh Wahyu; Raihan, Dany Zaky (2020)
Indonesia is a high-risk natural disaster country. Flash floods are one of the disasters that causes property loss and even lead to death. Approximately 63.7 million of the population in Indonesia live in high-risk areas. FLAMINGELD is designed for three statuses (Ready, Responsive, and Monitoring). The increased water generates hydrostatic pressure on the horizontal rods and lifts vertical rods that are arranged with slab like plates. As the water rises the barrier is lifted to form a 90° angle. In this state, the barrier will block the water stream. As the water level decrease, the sealing gasket will be released automatically enabled the barrier to close. On "Ready" status FLAMINGELD is focused on blocking the flow of the floods from 0° (closed condition) to 90° (open condition, perpendicular). On "Responsive" status FLAMINGELD is focused on sounding the standby signal alarm as the angle exceeds 90°.On "Monitoring" status FLAMINGELD can be monitored progressively in real time by the users from IoT based mobile application. It is intended as a longer-range interaction that makes it simpler for the users when they are inside or outside the house. The presence of FLAMINGELD can be a solution to prevent flash floods in Indonesia.